Clinical Outcomes in Atrial Fibrillation Patients With a History of Cancer Treated With Non-Vitamin K Antagonist Oral Anticoagulants: A Nationwide Cohort Study. Issue 10 (October 2021) - Chan, Yi-Hsin; Chao, Tze-Fan; Lee, Hsin-Fu; Chen, Shao-Wei; Li, Pei-Ru; Liu, Jia-Rou; Wu, Lung-Sheng; Chang, Shang-Hung; Yeh, Yung-Hsin; Kuo, Chi-Tai; See, Lai-Chu; Lip, Gregory Y.H.
Abstract : Background and Purpose: Data on clinical outcomes for nonvitamin K antagonist oral anticoagulant (NOACs) and warfarin in patients with atrial fibrillation and cancer are limited, and patients with active cancer were excluded from randomized trials. We investigated the effectiveness and safety for NOACs versus warfarin among patients with atrial fibrillation with cancer. Methods: In this nationwide retrospective cohort study from Taiwan National Health Insurance Research Database, we identified a total of 6274 and 1681 consecutive patients with atrial fibrillation with cancer taking NOACs and warfarin from June 1, 2012, to December 31, 2017, respectively. Propensity score stabilized weighting was used to balance covariates across study groups. Results: There were 1031, 1758, 411, and 3074 patients treated with apixaban, dabigatran, edoxaban, and rivaroxaban, respectively. After propensity score stabilized weighting, NOAC was associated with a lower risk of major adverse cardiovascular events (hazard ratio, 0.63 [95% CI, 0.50–0.80]; P =0.0001), major adverse limb events (hazard ratio, 0.41 [95% CI, 0.24–0.70]; P =0.0010), venous thrombosis (hazard ratio, 0.37 [95% CI, 0.23–0.61]; P <0.0001), and major bleeding (hazard ratio, 0.73 [95% CI, 0.56–0.94]; P =0.0171) compared with warfarin. The outcomes were consistent with either direct thrombin inhibitor (dabigatran) or factor Xa inhibitor (apixaban, edoxaban, and rivaroxaban) use, among patients with stroke history, and among patients with different type of cancer and local, regional, or metastatic stage of cancer ( P interaction >0.05). When compared with warfarin, NOAC was associated with lower risk of major adverse cardiovascular event, and venous thrombosis in patients aged <75 but not in those aged ≥75 years ( P interaction <0.05). Conclusions: Thromboprophylaxis with NOACs rather than warfarin should be considered for the majority of the atrial fibrillation population with cancer. Abstract : Supplemental Digital Content is available in the text.